1998
DOI: 10.1074/jbc.273.23.14071
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriGenerates Superoxide Radicals and Modulates Nitric Oxide Metabolism

Abstract: During studies of the bactericidal action of nitric oxide (NO), we found that it reversibly inhibited the respiration of Escherichia coli and irreversibly inhibited the respiration of Helicobacter pylori. Peroxynitrite, a reaction product of NO and superoxide, irreversibly inhibited the respiration of both H. pylori and E. coli. H. pylori, but not E. coli, generated substantial amounts of superoxide radicals. These results suggest that NO directly inhibits the respiration of E. coli whereas it rapidly reacts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 29 publications
3
70
0
Order By: Relevance
“…ROS enhance APE-1/Ref-1 expression and activity in fibroblasts, macrophages, B cells, and other cell types (25)(26)(27)(28). Studies have shown that infection with H. pylori generates ROS (29), resulting in the accumulation of ROS within the gastric mucosa (18) including the epithelial cells (30), which, in turn, leads to oxidative DNA damage (31) in infected patients. Previously, we reported that treatment with hydrogen peroxide as well as infection with H. pylori, but not Campylobacter jejuni, enhanced APE-1/Ref-1 expression in human gastric epithelial cells (32).…”
Section: Interleukin-8 Induction By Helicobacter Pylori In Gastric Epmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS enhance APE-1/Ref-1 expression and activity in fibroblasts, macrophages, B cells, and other cell types (25)(26)(27)(28). Studies have shown that infection with H. pylori generates ROS (29), resulting in the accumulation of ROS within the gastric mucosa (18) including the epithelial cells (30), which, in turn, leads to oxidative DNA damage (31) in infected patients. Previously, we reported that treatment with hydrogen peroxide as well as infection with H. pylori, but not Campylobacter jejuni, enhanced APE-1/Ref-1 expression in human gastric epithelial cells (32).…”
Section: Interleukin-8 Induction By Helicobacter Pylori In Gastric Epmentioning
confidence: 99%
“…Studies have shown that AP-1 and NF-B are redox-responsive elements (12) and that the generation of ROS by H. pylori (29) may trigger their activation in gastric epithelial cells. Furthermore, APE-1/Ref-1 itself is regulated by ROS and other environmental stimuli (25,26,28,61), and it has been suggested that the induction of IL-8 and other chemokines by H. pylori is redox sensitive and may depend on ROS-mediated activation of NF-B and AP-1 in gastric epithelial cells (17).…”
Section: Ape-1/ref-1 Is Involved In Il-8 Promoter Activationmentioning
confidence: 99%
“…Many studies have indicated that ROMs can directly interact with genomic DNA and cause damage in specific genes that control cell growth and differentiation [46][47][48] . Furthermore, it has been reported that intact H. pylori, as well as isolated cellular components, stimulate nitric oxide (NO) synthesis [49][50][51] . High concentrations of NO induce wild-type p53 protein accumulation [52,53] , and the NO-related deamination of DNA has been reported to cause GC-AT transitions, which are frequently found in p53 mutations in gastric cancer [23,54] .…”
Section: Oxidative Dna Damage and P53mentioning
confidence: 99%
“…This cascade is associated with the host immune response and alterations of vascular permeability, as a result of released vasoactive substances (15). Superoxide radicals and nitric oxide are also produced (16). Therefore, the prolonged oxidative injury caused by the persistent infection and the release of vasoactive substances might be involved in regional cerebral blood flow changes during migraine (4).…”
Section: Introductionmentioning
confidence: 99%